2007
DOI: 10.1111/j.1754-4505.2007.tb00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe tongue injury in an adolescent with epilepsy: A case report

Abstract: Epilepsy and other neurological disorders can have profound social, physical and psychological consequences, especially when they begin in childhood. Moreover, seizure episodes may cause fractures, burns, head injuries and oral injuries. This report presents a case history of an adolescent with a severe tongue injury related to epileptic seizures and outlines the proposed treatment, which included use of a maxillary silicone bite guard that allowed healing of the tongue injury within a few months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The possibility of tongue bite is higher unless ES is controlled. Cerqueira et al showed that the silicone bite guard protected the tongue from recurrent bites due to ES 9 . It was difficult in the present cases to obtain impressions for dental models and to apply the bite guard because of intellectual disability.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The possibility of tongue bite is higher unless ES is controlled. Cerqueira et al showed that the silicone bite guard protected the tongue from recurrent bites due to ES 9 . It was difficult in the present cases to obtain impressions for dental models and to apply the bite guard because of intellectual disability.…”
Section: Discussionmentioning
confidence: 67%
“…Roberge et al stated that injuries from tongue bites due to ES are mostly 1.5 cm or smaller, and do not represent a complication requiring any form of immediate response 5 . However, recurrent tongue bites caused by ES incur severe tongue injuries that lead to scarring, bleeding, and dysfunction in patients with mental retardation and refractory epilepsy 9 …”
Section: Introductionmentioning
confidence: 99%
“…Tongue lacerations, like scalp lacerations, are extremely vascular, tend to gape and can lead to significant blood loss . Although repair is usually straightforward, it must be closed with heavier suture material (3‐O) to prevent later dehiscence because of muscular action .…”
Section: Dentoalveolar Injuriesmentioning
confidence: 99%
“…9,10,23 Tongue lacerations, like scalp lacerations, are extremely vascular, tend to gape and can lead to significant blood loss. [24][25][26] Although repair is usually straightforward, it must be closed with heavier suture material (3-O) to prevent later dehiscence because of muscular action. 25 Intubation might be required to protect the airway and prevent further injury in unconscious patients who repeatedly bite their tongue.…”
Section: Soft Tissue Injuriesmentioning
confidence: 99%